2013
DOI: 10.1093/jxb/ert185
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis HEAT SHOCK TRANSCRIPTION FACTORA1b overexpression enhances water productivity, resistance to drought, and infection

Abstract: Heat-stressed crops suffer dehydration, depressed growth, and a consequent decline in water productivity, which is the yield of harvestable product as a function of lifetime water consumption and is a trait associated with plant growth and development. Heat shock transcription factor (HSF) genes have been implicated not only in thermotolerance but also in plant growth and development, and therefore could influence water productivity. Here it is demonstrated that Arabidopsis thaliana plants with increased HSFA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 90 publications
4
119
0
Order By: Relevance
“…For cDNA synthesis for real-time qPCR and RT-PCR, 1 µg total RNA was treated with RNase-free DNase (Ambion) according to the manufacturer's instructions and reverse transcribed as previously described (Ball et al, 2004). qPCR-PCR was performed using a SYBR green fluorescence-based assay as described previously (Bechtold et al, 2010(Bechtold et al, , 2013. Gene-specific cDNA amounts were calculated from threshold cycle (Ct) values and expressed relative to controls and normalized with respect to ACTIN and CYCLOPHILIN cDNA according to Gruber et al (2001).…”
Section: Rt-pcr and Qpcrmentioning
confidence: 99%
See 1 more Smart Citation
“…For cDNA synthesis for real-time qPCR and RT-PCR, 1 µg total RNA was treated with RNase-free DNase (Ambion) according to the manufacturer's instructions and reverse transcribed as previously described (Ball et al, 2004). qPCR-PCR was performed using a SYBR green fluorescence-based assay as described previously (Bechtold et al, 2010(Bechtold et al, , 2013. Gene-specific cDNA amounts were calculated from threshold cycle (Ct) values and expressed relative to controls and normalized with respect to ACTIN and CYCLOPHILIN cDNA according to Gruber et al (2001).…”
Section: Rt-pcr and Qpcrmentioning
confidence: 99%
“…This involves treatments such as cutting and air drying leaves and/or roots or induction of osmotic shock through the application of highly concentrated osmotica such as polyethylene glycol or mannitol (Kreps et al, 2002;Seki et al, 2002;Kawaguchi et al, 2004;Kilian et al, 2007;Weston et al, 2008;Fujita et al, 2009;Abdeen et al, 2010;Deyholos, 2010;Mizoguchi et al, 2010). These experiments have substantially increased our knowledge of molecular responses under severe drought stress, but they do not always reflect physiological conditions experienced by drought-stressed soil-grown plants (Bechtold et al, 2010(Bechtold et al, , 2013Harb et al, 2010;Wilkins et al, 2010;Lawlor, 2013;Zhang et al, 2014). Physiological responses such as stomatal conductance, photosynthetic performance, and metabolic changes are usually not measured during the progression of the drought stress, and the varied nature of the stress induction treatments makes comparative analysis between experiments problematic.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that ROS directly inhibit/modify redox-sensitive proteins like phosphatases (Apel and Hirt 2004) and heat shock transcription factors (HSFs; Miller and Mittler 2006). Overexpression of the Arabidopsis thaliana gene encoding HSF-A1b confers enhanced resistance to both drought and bacterial infection, and this response is dependent on H 2 O 2 signaling (Bechtold et al 2013). Transcriptome analysis of rice revealed that HSF binding sites were significantly enriched in promoters of up-regulated genes in response to cold, heat, and oxidative stress suggesting a role of HSFs as central regulators of plant stress responses that involve ROS accumulation, e.g., disease resistance (Mittal et al 2012).…”
Section: Expression Of Ros-related Genes and Their Functions In Plantmentioning
confidence: 99%
“…2D). By contrast, 171 labeled probes mutated (to TAAGTCCCTAAAC (AtPDX1.2 HSEmI) or GAAGTTAAAAAAC 172 (AtPDX1.2 HSE mII)) (Bechtold et al, 2013) in the HSE motif failed to recruit HSFA1b (i.e. no 173 mobility shift).…”
mentioning
confidence: 99%